WANITA PENGUSAHA CERDAS BERSOSIAL MEDIA MENGEMBANGKAN UMKM FASHION - Annisa Indah Sari; Titis Tatasari; Anisyah Rahmadani; Kintan Andela (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Along with the excellent development of Indonesia's fashion industry, business competition is currently heating up. Concurrently, micro, small, and medium-sized enterprises (MSMEs) are expanding at a rapid pace, particularly in Surabaya. In order to thrive in today's cutthroat business environment, it is crucial to devise strategies for business development. One of the fashion-related businesses in Surabaya that sells hijab items is Cuties Hijab. Cuties Hijab product sales continue to be highly unpredictable and have even been known to fall as the company has progressed. The company's stagnating position and low product sales are the consequence of multiple challenges, including insufficient human resources and weak product promotion. This situation provides context for why this study is important; its goal is to analyze internal and external issues affecting Cuties Hijab in order to formulate an appropriate strategy for the company's future growth. Qualitative descriptive research is employed. Primary data comes from in-depth interviews, while secondary data comes from a variety of sources like books, records, and the internet. The IFE Matrix, QSPM, IE, SWOT, and IFE are the analytical tools that are utilized. According to the findings from the strategy analysis conducted at the decision-making stage, the market penetration strategy is the best course of action for Cutis Hijab.